The The Students’ Perceptions on Making Digital Video Project to Develop Their Speaking Skills - Cholimatus Zuhro; Agus Setia Budi (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to explore students' perceptions of creating digital video projects as a tool for teaching and improving speaking abilities. A descriptive qualitative research design was applied, involving 50 students enrolled in the Intermediate English course during the second semester of the Machine Automotive Study Programme at Politeknik Negeri Jember. Data collection techniques included questionnaires distributed via Google Forms, consisting of multiple-choice and open-ended questions, complemented by semi-structured interviews to gain deeper insights. The focus was on understanding how students perceive the effectiveness of digital video projects in enhancing their speaking skills and overall language learning experience. The findings revealed that most students had a positive attitude toward creating digital video projects, stating that such activities significantly enhanced their confidence, fluency, and pronunciation in English. Many participants emphasized that digital video projects encouraged them to practice speaking repeatedly, which contributed to reducing anxiety and improving their performance. The study also found a clear connection between students' intrinsic motivation to improve their speaking skills and the perceived benefits of completing digital video tasks. Additionally, students highlighted the creative aspect of video-making, which fostered collaboration, critical thinking, and self-expression. The role of the lecturer was identified as crucial in guiding students throughout the project, particularly in overcoming technical and linguistic challenges. The study concludes that integrating digital video projects into speaking lessons not only improves speaking ability but also motivates learners to take active participation in language learning.